An Evaluation of Public Expenditure and Economic Growth in Nigeria Using the Sectorial Economic Function Approach - Duruibe, Stanley Chigozie; Chigbu, Emmanuel E.; Ejezube, Emeka Eugene; Nwauwa, Philip Gospel (European Scientific Journal, ESJ, 2020)
This study investigates the effect of government public expenditures on Nigeria’s economic growth and development using the sectorial economic function approach. The real Gross Domestic Product (GDP), which is the outcome variable in this study, was employed as the proxy for economic growth while government’s expenditures on administrative services, economic services, social and community services, and transfers were used as the predictor variables in this study. Surprisingly, the results from the cointegration test and Vector Error Correction Model estimate reveal that all the predictor variables, apart from expenditure on administration, have a positive relationship with economic growth. While expenditures on economic services and social and community services have positive and significant relationship with economic growth, government transfers has a positive but insignificant relationship with economic growth. Emphatically, expenditure on administrative services has a significant negative relationship with economic growth. The result from Wald coefficient diagnostic test reveals that there is short run causality running from the public expenditure aggregates to economic growth. Thus, this study recommends, among others, that efforts should be made to reduce the deadweight aggregate public expenditure on administrative services since it has a significant negative impact on economic growth trend in Nigeria.